KETERKAITAN ANTARA PERSEPSI PENTINGNYA AKREDITASI RUMAH SAKIT DENGAN PARTISIPASI, KOMITMEN, KEPUASAN KERJA, DAN KINERJA KARYAWAN - Hendroyogi, Safil; Harsono, Mugi (Universitas Muhammadiyah Surakarta, 2016)
Accreditation of hospitals is very important to do as an effort to improve quality and patient safety. Many of the standards that must be implemented in hospitals, requiring an optimal role for all stakeholders (stakeholders), especially the participation of employees. This condition greatly be affected by employees’ perception of the benefits of hospital accreditation. The purpose of the study is to examine employee perceptions about the benefits of accreditation associated with participation, satisfaction, commitment and employee performance. The benefits of this research are expected to be input for the hospital management, to encourage all employees to learn about the hospital accreditation standards. Data from the study was obtained by means of a survey of hospital employees, using a Likert scale. Furthermore, the data do tests of validity and reliability and path analysis (path analysis), to see the correlation between variables. Research conducted on 259 randomly selected respondents, composed of physicians, nurses, medical support, as well as administrative personnel. The results of this studyindicate that there is significant influence between the perception of the benefits ofaccreditation to the participation of accreditation with a significance level of 0.000, the perception of the benefits of accreditation with the organizational commitment amounting to 0,016, the perception of the benefits of accreditation and job satisfaction amounting to 0,000, participation accreditation with organizational commitment amounting to 0,039, accreditation participation with satisfaction employment amounting to 0,000, accreditation participation with performance amounting to 0,000, job satisfaction with organizational commitment amounting to 0,039, organizational commitment with performance amounting to 0,018, job satisfaction with performance amounting to 0.000.